Striatal cholinergic interneuron pause response requires Kv1 channels, is absent in dyskinetic mice, and is restored by dopamine D5 receptor inverse agonism - Cecilia Tubert; Rodrigo Manuel Paz; Agostina Mónica Stahl; Kianny Miroslava Sanchez Armijos; Lorena Rela; Mario Gustavo Murer (eLife, 2025)
Striatal cholinergic interneurons (SCINs) exhibit pause responses conveying information about rewarding events, but the mechanisms underlying these pauses remain elusive. Thalamic inputs induce a pause mediated by intrinsic mechanisms and regulated by dopamine D2 receptors (D2Rs), though the underlying membrane currents remain unknown. Moreover, the role of D5 receptors (D5Rs) has not been addressed so far. Here, we performed ex vivo studies showing that glutamate released by thalamic inputs in the dorsolateral striatum induces a burst in SCINs, followed by a pause mediated by the activation of a Kv1-dependent delayed rectifier current. Endogenous dopamine promotes this pause through D2R stimulation, while pharmacological stimulation of D5Rs suppresses it. Remarkably, this pause is absent in parkinsonian mice rendered dyskinetic by chronic L-DOPA treatment but can be reinstated acutely by the inverse D5R agonist clozapine. Blocking the Kv1 current eliminates the pause reinstated by the D5R inverse agonist. In contrast, the D2-type receptor agonists quinpirole and sumanirole failed to reinstate a pause in dyskinetic mice. In conclusion, stimulation of thalamic inputs induces excitation followed by a pause in SCINs, which is lost in parkinsonian mice that have been rendered dyskinetic. This pause is mediated by delayed rectifier Kv1 channels, which are tonically blocked in dyskinetic mice by a mechanism depending on D5R ligand-independent activity. Targeting these alterations may have therapeutic value in Parkinson’s disease.